MERANCANG MANAJEMEN AGRIBISNIS SYARIAH DI DESA CIBITUNG TENGAH, KECAMATAN TENJOLAYA, KABUPATEN BOGOR - Ria Kusumaningrum; Susi Melinasari; Siti Maspupah (SAHID EMPOWERMENT JOURNAL, 2022)
Community service in which there are community empowerment activities is a development process in which the community takes the initiative to start a process of social activity to improve their own situation and condition. Central Cibitung Village, Tenjolaya District, Bogor Regency as an Agropolitan area which has been designated as an agribusiness development that is not limited to horticultural agriculture, but this stipulation is expected to be one of the steps to improve the community's economy. One of the government's efforts to empower farming communities is through the Rural Agribusiness Development (PUAP) program. PUAP begins with the process of increasing the capacity of human resources as executors of PUAP activities in the field. At the same time, this community service activity can use PUAP to overcome problems from the aspects of capital, market access and technology and the still weak management of farming businesses which causes powerlessness in farming communities in Central Cibitung Village, Tenjolaya District, Bogor Regency.